(untitled) (New York, 2012)
Dirty Dancing is a timeless love story set in the summer of 1963 when Baby, an innocent seventeen-year-old, meets Johnny, a dashing hotel dance instructor at Kellerman’s Catskills resort. Its passionate story line and alluring dance numbers made the film a box-office hit and pop-culture phenomenon. Though the film launched the careers of stars Patrick Swayze and Jennifer Grey, and won an Academy Award®, a Golden Globe®, a Grammy Award®, and an Independent Spirit Award®, it is best known for being an undeniably loved, oft-quoted piece of American cinematic history.
Keywords: Khiêu vũ bẩn (Hình ảnh chuyển động),Dirty dancing (Motion picture)